The broad movements of criminal interests. Maps and emerging problems in the new global world (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
This article explores the evolving landscape of organized crime through a five-pronged analytical lens. It highlights (1) the increasing centrality of the Eastern Hemisphere in global criminal dynamics and (2) the rapid ascent of new criminal organizations. Particular attention is given to (3) the expanding role of mercenary companies, which blur the lines between illicit enterprise and armed conflict. The paper also examines (4) a significant geographical and productive shift in the drug trade, alongside (5) the emergence of fluid transnational alliances. These developments challenge traditional analytical frameworks and call for renewed scholarly engagement and interdisciplinary openness in the study of contemporary organized crime.
Keywords: Organized Crime; Great Disorder; Wars; Change; Compass